The physical exercises benefits in arterial hypertension - Kirinus, Graciela (2011)
The high blood pressure is a prevalent risk factor. The physical exercise, an efficient non-medicine option in prevention, control and treatment of its on. This present study had the objective to verify through a bibliographic research the benefits of physical exercises in arterial hypertension. Were found in the literature, 9 articles, all national printed in magazines about health, physical exercise and arterial hypertension in hypertensive humans. It was verified that different physical exercises programs as: aerobic, strength and located muscular resistance shown reduction in arterial pressure values. The values of reduction in arterial pressure vary as the number of the exercises, the time study and individual factors as the value of arterial pressure pre-test, associated diseases and corporal composition. A pondered decreasing and on the body fat perceptual and a better cardiac respiration had a good influential in these values reduction. Physical activities shown to be beneficial for hypertenses verifying a decreasing in arterial pressure and others variables already mentioned.